Evolutionary Dynamics of Polintons: A Rarely Investigated Superfamily of DNA Transposons - Khan, Muhammad Umair; Nouroz, Faisal; Waheed, Amina; Noreen, Shumaila (Current Trends in OMICS, 2024)
Polintons, also known as ‘Maverick’ is a rarely investigated superfamily of DNA transposons. Although, discovered in recent decades, these elements are now found in several eukaryotic genomes due to the advancements and expansions in genome sequencing projects. The current study was conducted to investigate the evolutionary genomics and distribution of Polintons in various genomes. Approximately, 102 Polinton elements from various species were collected from Repbase – GIRI database. They have shown a high structural diversity and ranged in sizes from 03 to 42kb. The phylogenetic relationship and evolutionary history of the Polinton superfamily was investigated using bioinformatics software. Phylogenetic trees were created based on two major protein coding domains, such as RVE integrase and DNA POL B. In both cases, the sequences were clustered in 2 clades, several sub-clades, and groups with variable number of elements in each group. The cladograms represented the extensive genetic diversity and evolutionary history of these elements and allowed to observe the intricate branching patterns and relationships within the Polinton superfamily. The cladogram provides a roadmap to explore the relationships and dynamics of the Polinton superfamily in detail. The current study aimed to enhance the understanding of evolutionary dynamics of Polintons found in different organisms.